Re-diagnosis of diabetes mellitus type 1 to maturity-onset diabetes of the young type 2 (MODY 2) in a 26-year-old male: a case report - Siudek, Bartosz; Dróżdż, Olgierd; Bińczyk, Wiktoria; Lissak, Karina; Nowińska, Bianka; Brzozowska, Patrycja; Wiśniewska, Anna (Quality in Sport, 2024)
Diabetes mellitus (DM) encompasses a spectrum of metabolic disorders characterized by hyperglycemia due to defects in insulin secretion, action, or both. Type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) are the most prevalent forms, whereas Maturity-Onset Diabetes of the Young (MODY) represents a monogenic subtype, often misdiagnosed due to its phenotypic overlap. This case study highlights a 26-year-old male initially diagnosed with T1DM at age 12, managed with insulin therapy. Upon admission, despite stable glycemic control and preserved C-peptide secretion, genetic testing revealed MODY 2 due to a variant in the GCK gene. Unlike T1DM and T2DM, MODY 2 is characterized by mild, persistent hyperglycemia with a low risk of complications, emphasizing the importance of genetic diagnosis for tailored management and family counseling. This case underscores the critical role of genetic evaluation in accurately diagnosing and managing atypical diabetes presentations.